Shape of Social Forestry in Rural India in the 21st Century - Shah, S. A. (Indian Forester, 1989)
Multiple use of land and use of multi-purpose indigenous trees with a proven merit for improving fertility status of soil would govern Social Forestry practices in the 21st century. It requires strong support of new research dim nsions with well trained persons. The active role of Government and voluntary organisations is necessary for proper implementation of Social Forestry programme. Social Forestry of the 21st century will be a self-propelling, selfsustaining and largely a self-reliance movement of the people. Govt. would provide the required finance, Technology and market facilities.